Association of grip strength, sleep duration, and comorbidities with depressive symptoms in middle-aged and older patients with chronic lung diseases: a cross-sectional network analysis based on CHARLS data - Lu Li; Jiaqi Meng; Yinxiang Wu; Xiaoyuan Bu; Liping Gao; Zhiwei Xiao; Jiquan Chen (Frontiers in Psychology)
BackgroundDepressive symptoms are prevalent among patients with chronic lung diseases (CLDs) and adversely impact their quality of life. This study aims to explore the association of grip strength (GS), sleep duration, and comorbidities with depressive symptoms in patients with CLDs, with an in-depth analysis of the underlying mechanisms.MethodsBased on data from the China Health and Retirement Longitudinal Study (CHARLS), this study included participants aged 45 and above with diagnosed CLDs. Depressive symptoms were assessed using the 10-item Center for Epidemiologic Studies Depression Scale (CESD-10). Binary logistic regression, subgroup analysis, and network analysis were conducted to examine the intricate relationships between GS, sleep duration, comorbidities, and specific depressive symptoms.ResultsAmong the 1,427 participants, 39.8% exhibited depressive symptoms. Adjusted analyses revealed that GS (OR = 0.964, p < 0.001) and sleep duration (OR = 0.808, p < 0.001) were negatively associated with depressive symptoms, whereas the number of comorbid chronic diseases (OR = 1.189, p < 0.001) showed a significant positive correlation with depressive symptoms. Subgroup analyses demonstrated variations in these relationships across different demographic characteristics and lifestyle factors. Network analysis pinpointed “depressed” as the core symptom, with “annoyed,” “exhausted,” and “lonely” as secondary core symptoms. The robust associations between specific factors and depressive symptoms (GS with “annoyed,” sleep and comorbid chronic diseases with “depressed”) suggested potential targets for interventions.ConclusionThis study underscores the complex interplay of GS, sleep duration, and comorbidities with depressive symptoms in patients with CLDs. These findings offer new perspectives for improving the mental health of this vulnerable population.